2020
DOI: 10.3390/brainsci10110805
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Disorders: Effect of High-Fat Diet on Synaptic Plasticity and Mitochondrial Functions

Abstract: Neurodevelopmental disorders (NDDs) include diverse neuropathologies characterized by abnormal brain development leading to impaired cognition, communication and social skills. A common feature of NDDs is defective synaptic plasticity, but the underlying molecular mechanisms are only partially known. Several studies have indicated that people’s lifestyles such as diet pattern and physical exercise have significant influence on synaptic plasticity of the brain. Indeed, it has been reported that a high-fat diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 143 publications
1
11
0
Order By: Relevance
“…Data from the array allowed us to raise several points: (1) Chronic HFD feeding caused disruption in energetic metabolic pathways. This would be in accordance with previous reports in the field in which HFD has been demonstrated to disrupt physiological metabolism and promote insulin resistance, as well as obesity and other pathological alterations (Tsan et al 2021 ; Leigh and Morris 2020 ; Penna et al 2020 ). Increased ingestion of fats, obesity and resistance to hormones like insulin caused disturbances in normal cognitive function and structures as reported by our research team and others (Tsan et al 2021 ; Leigh and Morris 2020 ; Penna et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Data from the array allowed us to raise several points: (1) Chronic HFD feeding caused disruption in energetic metabolic pathways. This would be in accordance with previous reports in the field in which HFD has been demonstrated to disrupt physiological metabolism and promote insulin resistance, as well as obesity and other pathological alterations (Tsan et al 2021 ; Leigh and Morris 2020 ; Penna et al 2020 ). Increased ingestion of fats, obesity and resistance to hormones like insulin caused disturbances in normal cognitive function and structures as reported by our research team and others (Tsan et al 2021 ; Leigh and Morris 2020 ; Penna et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that, due to the bidirectional communication between the immune system and the brain [13], cytokine levels are able to modulate neuronal function and behavioral processes [14]. Moreover, multiple lines of evidence from genetic linkage studies on animal models have highlighted aberrant brain plasticity in the pathophysiology of ASD, including altered neurogenesis, neurite outgrowth, synaptogenesis, and synaptic plasticity [15][16][17]. In this scenario, a key role is played by the hippocampus, a brain region where active neurogenesis and long-term changes of synaptic strength take place [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that a high-fat diet can affect embryonic development. Studies have shown that long-term high-fat diets can cause mitochondrial dysfunction and affect the offspring's synapses development [23]. When the embryos of the three groups continued to develop to 12.5d and 14.5d, it was observed that the cells in the neural tube of the Mex3c group and the HFD group were small and scarce.…”
Section: Discussionmentioning
confidence: 98%
“…Long-term high-fat diet can cause lipid deposition, increase fat, break the balance of human lipid metabolism, and induce non-alcoholic fatty liver. Studies have shown that long-term high-fat diet during pregnancy can affect offspring neurites by damaging mitochondrial function [13]; that a high-fat diet can lead to changes in mitochondrial function, which in turn leads to lipid metabolism disorders and neurodevelopment. Professor Lu of the research group has proved in previous experiments that Mex3c gene-de cient mice induce the body to form a negative energy state [14] and other studies have shown that without inhibiting food intake, Mex3c mutations can contribute to glucose and lipid metabolism, resulting in decreased blood glucose and blood lipid concentrations in mice, and increased insulin effect, making Mex3c resistant to obesity caused by food [15,16].…”
Section: Introductionmentioning
confidence: 99%